Developing of Mathematical Process for Solving Problem according to the PISA framework with Problem based Learning Activity for Mathayomsuksa 4 Students - Permcheewa, Jiranuwat; Cojorn , Kanyarat (Journal of Roi Et Rajabhat University, 2024)
The purposes of this research were 1) to develop a problem-based lesson plan with an efficiency of 75/75, 2) to compare the Mathematical process for solving problem using problem-based learning activities against the 75 percent criteria and 3) to compare learning achievements using problem-based learning activities against the 75 percent criteria. The samples were 39 students of Mathayomsuksa 4 in the 1st semester of 2023 academic year at Mahasarakham University Demonstration School (Secondary) which were obtained by cluster random sampling. The research instruments included 1) learning management plans, 2) the Mathematical process for solving problem and 3) learning achievement test. Statistics used in this study consisted of percentage, means, standard deviation and one sample t-test. The research findings were as follows; 1) The learning activities using the learning activities based on problem-based learning had an effective (E1/E2) of 86.50/82.65 which were higher than the specified criteria. 2) The Mathematical process for solving problem of the student was higher than the specified threshold of 75 percent with the statistically significant at the .05 level. 3) The learning achievement of the students were higher than the specified threshold of 75 percent with the statistically significant at the .05 level.